2020
DOI: 10.1111/dth.14024
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of psychodermatology in Indian dermatologists: A South Indian perspective

Abstract: This study was aimed to survey the awareness, knowledge, practicing patterns, and attitudes of dermatologists toward psychocutaneous disorders in a South Indian State. The questionnaire-based study was performed from August 1 to October 31, 2019. Study participants included 123 dermatologists. The questionnaire consisted of nine multiple-choice questions and two open-ended questions regarding knowledge, practicing patterns, and attitude to psychodermatology. Forty five (36.6%) dermatologists completed this onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
(48 reference statements)
1
14
0
Order By: Relevance
“…In a Turkish study, 11 hyperhidrosis, atopic dermatitis, and vitiligo were described to be the commonest psychocutaneous disorder reported by dermatologists while two studies from Iran and United Arab Emirates (UAE) reported acne, alopecia, and vitiligo to be the most frequently seen psychocutaneous disordes 12,13 . A study from southern India reported vitiligo to be the most common psychocutaneous disorder 14 . This could possibly could be explained due to local cultural factors emphasizing on the color of skin.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a Turkish study, 11 hyperhidrosis, atopic dermatitis, and vitiligo were described to be the commonest psychocutaneous disorder reported by dermatologists while two studies from Iran and United Arab Emirates (UAE) reported acne, alopecia, and vitiligo to be the most frequently seen psychocutaneous disordes 12,13 . A study from southern India reported vitiligo to be the most common psychocutaneous disorder 14 . This could possibly could be explained due to local cultural factors emphasizing on the color of skin.…”
Section: Discussionmentioning
confidence: 99%
“…Variable degrees of psychodermatology awareness and knowledge among dermatologists are reported worldwide. Two studies, from Turkey 11 and the Middle East, 12 reported 33% good understanding of what psychodermatology is while only 18%, 10%, 31%, and 0% of respondents in Washington State, 4 Albania, 15 southern India, 14 and Kazakhstan 5 , respectively, understood what the exact concept of PD is.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations